Acute acalculous cholecystitis caused by SARS-CoV-2 infection: A case report and literature review. (January 2022) - Futagami, Hana; Sato, Hiroki; Yoshida, Ryuichi; Yasui, Kazuya; Yagi, Takahito; Fujiwara, Toshiyoshi
Abstract: Background: Emerging data indicate that gastrointestinal disorders, in addition to pulmonary dysfunction, are also hallmarks of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Case presentation: A 42-year-old man with maintenance hemodialysis developed high fever and dyspnea. He was positive for SARS-CoV-2 and was diagnosed with pneumonia. After treatment for SARS-CoV-2, his respiratory condition improved. However, he developed right upper quadrant pain with elevated inflammatory markers (white blood cells, 21, 160/μL; c-reactive protein, 163.9 mg/L) on the 13th day. Abdominal computed tomography revealed acute acalculous cholecystitis. Percutaneous transhepatic gallbladder drainage (PTGBD) was performed together with antibiotic therapy, which resulted in improvement of symptoms. Laparoscopic cholecystectomy was performed 36 days after PTGBD. Conclusion: We report a rare case of acute acalculous cholecystitis (AAC) following pneumonia caused by SARS-CoV-2 infection. We also conducted a literature search to characterize SARS-CoV-2-related cholecystitis. Infection with SARS-CoV-2 is an important trigger for AAC, and appropriate therapeutic alternatives should be cautiously selected according to individual cases. Highlights: We experienced a case of acute acalculous cholecystitis (AAC) following COVID-19. We conducted a literature review to explore clinical features of COVID19 related AAC. SARS-CoV-2 infection should be considered as an important trigger for AAC.